SMA Identified: Clinical and Molecular Findings From a Sponsored Testing Program for Spinal Muscular Atrophy in More Than 2,000 Individuals - Bowen, B. Monica; Truty, Rebecca; Aradhya, Swaroop; Bristow, Sara L.; Johnson, Britt A.; Morales, Ana; Tan, Christopher A.; Westbrook, M. Jody; Winder, Thomas L.; Chavez, Juan C. (Frontiers in Neurology, 2021)
Background: Spinal muscular atrophy (SMA) linked to chromosome 5q is an inherited progressive neuromuscular disorder with a narrow therapeutic window for optimal treatment. Although genetic testing provides a definitive molecular diagnosis that can facilitate access to effective treatments, limited awareness and other barriers may prohibit widespread testing. In this study, the clinical and molecular findings of SMA Identified—a no-charge sponsored next-generation sequencing (NGS)-based genetic testing program for SMA diagnosis—are reported. Methods: Between March 2018 and March 2020, unrelated individuals who had a confirmed or suspected SMA diagnosis or had a family history of SMA were eligible. All individuals underwent diagnostic genetic testing for SMA at clinician discretion. In total, 2,459 individuals were tested and included in this analysis. An NGS-based approach interrogated sequence and copy number of SMN1 and SMN2. Variants were confirmed by multiplex ligation-dependent probe amplification sequencing. Individuals were categorized according to genetic test results: diagnostic (two pathogenic SMN1 variants), nearly diagnostic (SMN1 exon-7 deletion with a variant of uncertain significance [VUS] in SMN1 or SMN2), indeterminate VUS (one VUS in SMN1 or SMN2), carrier (heterozygous SMN1 deletion only), or negative (no pathogenic variants or VUS in SMN1 or SMN2). Diagnostic yield was calculated. Genetic test results were analyzed based on clinician-reported clinical features and genetic modifiers (SMN2 copy number and SMN2 c.859G>C). Results: In total, 2,459 unrelated individuals (mean age 24.3 ± 23.0 years) underwent diagnostic testing. The diagnostic yield for diagnostic plus nearly diagnostic results was 31.3% (n = 771/2,459). Age of onset and clinical presentation varied considerably for individuals and was dependent on SMN2 copy number. Homozygous deletions represented the most common genetic etiology (96.2%), with sequence variants also observed in probands with clinical diagnoses of SMA. Conclusions: Using a high-yield panel test in a no-charge sponsored program early in the diagnostic odyssey may open the door for medical interventions in a substantial number of individuals with SMA. These findings have potential implications for clinical management of probands and their families.